PESAN KEMANUSIAAN DALAM FILM THE SHAPE OF WATER (STUDI ANALISIS SEMIOTIK ROLAND BARTHES) - Wijaya, Marini Fransiska; Sugiarica Joni, I Dewa Ayu; Amanda Gelgel, Ni Made Ras (E-Jurnal Medium; Vol 2 No 1 (2021): Jurnal Ilmu Komunikasi Vol 2 No 1 Tahun 2021, 2021)
Film is one of the communication media that has the ability to convey a message and becomes an effective and educative media as a reference for humanity for the community. One of the films that raises the message of various important issues in humanity is The Shape of Water. The purpose of this research is to explain the messages of humanity in the film The Shape of Water through a qualitative approach. This research uses the semiotic analysis of Roland Barthes to examine the meaning of denotation, connotation and myth contained in the film. The results of this research show that the human values in the The Shape of Water include messages of helping each other, realizing equality, having a good attitude towards others, establishing intimacy and affection, as well as reminding and advising each other.   Keyword: The Message of Humanity, Film, The Shape of Water, Semiotics Roland Barthes